Weather-resistant polyformaldehyde and preparation method thereof

By introducing TiO2 aerogel and PEI graft layer into polyformaldehyde, combining light stabilizer and ultraviolet absorber, the problem of polyformaldehyde being sensitive to ultraviolet light is solved, significantly improving its UV resistance and weather resistance, and extending the service life of the material.

CN119708751APending Publication Date: 2025-03-28HUBEI XINGFA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852127.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Polyformaldehyde is sensitive to ultraviolet light. Long-term exposure to outdoors will lead to photothermal aging, resulting in molecular degradation, degradation of mechanical properties, and material embrittlement, powdering, and cracking.

Method used

By preparing titanium dioxide (TiO2) aerogel and grafting polyethyleneimine (PEI) on the aerogel, the porous structure of TiO2 and the high specific surface area are used to absorb, reflect and shield the ultraviolet rays. At the same time, the introduced amine groups are reactively absorbed and eliminated formaldehyde, combined with polyformaldehyde, light stabilizer and ultraviolet absorber for composite, and processed by melt extrusion method to obtain polyformaldehyde composite materials with excellent UV weather resistance.

Benefits of technology

It significantly improves the UV resistance of polyformaldehyde, inhibits photodegradation, maintains the mechanical properties of the material, and extends its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses weather-resistant polyformaldehyde and a preparation method thereof, and the preparation method is characterized by comprising the following steps: researching and preparing titanium dioxide (TiO2) aerogel, and grafting polyethyleneimine (PEI) to the aerogel; the strong absorption, reflection and shielding effects of TiO2 on ultraviolet rays, the enhanced multi-time absorption / reflection effect formed by a porous structure, the adsorption effect of high porosity and specific surface area on formaldehyde generated by photodegradation of polyformaldehyde, and the reactive absorption and removal effects of a large number of introduced amido groups on formaldehyde are utilized, so that the formaldehyde adsorption effect is improved; the polyformaldehyde is compounded with polyformaldehyde, a light stabilizer, an ultraviolet light absorber and the like, and a conventional melt extrusion method is adopted for processing, so that the polyformaldehyde composite material with excellent ultraviolet resistance and weather resistance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to weather-resistant polyoxymethylene and a preparation method thereof, and belongs to the field of polymer material processing. Background Art

[0002] Polyoxymethylene (POM) is a thermoplastic engineering plastic with [-CH2-O-] as the main chain, no branching, high melting point, high density, and high crystallinity. It has excellent mechanical properties, creep resistance, fatigue resistance, wear resistance, self-lubricating properties, and chemical resistance. It is the closest type of engineering plastic to metal and is widely used in the fields of electronics, automobiles, machinery, light industry, and building materials. However, since the main chain of polyoxymethylene molecules is a CO bond, it is sensitive to ultraviolet light with a wavelength of 280-400 nm. When it is exposed to the outdoors for a long time, it will experience photothermal aging under ultraviolet radiation, causing its molecular degradation, significant decrease in mechanical properties, embrittlement, powdering, and cracking. The study of its anti-ultraviolet and weathering modification is of great significance for its practical application.

[0003] Ren Xiancheng et al., Elastomers, 2004-12-25, 14(6): 12-15, conducted ultraviolet aging experiments on homemade acrylic elastomer, antioxidants and light stabilizers and polyoxymethylene after melt blending. The mechanical properties and surface molecular weight of the samples before and after aging were tested. The results showed that the molecular weight of the modified polyoxymethylene was well maintained. The impact toughness and elongation at break are significantly better than those of unmodified polyoxymethylene; Wang Yatao et al., Plastic Industry, 2016, 44 (10): 96-99, conducted a long-term aging experiment on polyoxymethylene using a UV aging chamber, indicating that the combination of different free radical scavengers can achieve a good synergistic anti-light aging effect and significantly improve the mechanical property retention rate of polyoxymethylene materials; Tao Zhaozeng et al., China Plastics, 2014, 28 (4): 28-33, mixed dimethylsiloxane, UV absorber, light stabilizer, antioxidant, UV shielding agent, formaldehyde absorber with polyoxymethylene to prepare weather-resistant polyoxymethylene, indicating that the weathering additive improves the mechanical property retention rate of polyoxymethylene, and its aging process mainly occurs in the amorphous region, and it is particularly sensitive to light, followed by thermal oxygen, and less affected by water and heat. However, the introduction of conventional light stabilization system has limited improvement in the anti-ultraviolet performance of polyoxymethylene. Summary of the invention

[0004] In view of the urgent need for practical application of weather-resistant polyformaldehyde, the present invention provides a weather-resistant polyformaldehyde and a preparation method thereof, which are characterized by: studying and preparing titanium dioxide (TiO2) aerogel, and grafting polyethyleneimine (PEI) to the aerogel, utilizing the strong absorption, reflection and shielding effects of TiO2 on ultraviolet rays, the enhanced multiple absorption / reflection effects formed by its porous structure, the adsorption effects of its high porosity and specific surface area on formaldehyde generated by photodegradation of polyformaldehyde, and the reactive absorption and scavenging effects of a large number of introduced amino groups on formaldehyde, compounding it with polyformaldehyde, a light stabilizer, an ultraviolet absorber, etc., and processing it by a conventional melt extrusion method, so as to obtain a polyformaldehyde composite material with excellent anti-ultraviolet and weather-resistant properties.

[0005] The object of the present invention is achieved by the following technical measures, wherein the raw material fractions are all parts by weight unless otherwise specified.

[0006] A weather-resistant polyoxymethylene and a preparation method thereof include the following two steps: PEI-TiO2 aerogel preparation: The TiO2 aerogel is added to a solvent, the temperature is raised to 50-80°C, triethylamine and dibasic acid anhydride are added, and a reaction is performed to obtain a carboxylated TiO2 aerogel; N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added to the carboxylated TiO2 aerogel, the mixture is stirred evenly, and then PEI is added to react to obtain a PEI-grafted TiO2 aerogel, i.e., PEI-TiO2 aerogel; Preparation of weather-resistant polyoxymethylene: The polyoxymethylene and PEI-TiO2 aerogel particles are uniformly mixed at high speed, melt-kneaded, extruded and granulated to obtain weather-resistant polyoxymethylene.

[0007] The TiO2 aerogel is prepared by hydrolyzing a titanate alcohol solution under acidic conditions, adding formamide, and stirring to obtain a TiO2 alcohol gel. The obtained TiO2 alcohol gel is aged, soaked in an alcohol solution, and vacuum dried to obtain a TiO2 aerogel.

[0008] The alcohol solution is selected from C1-C4 alcohol solutions.

[0009] The dibasic acid anhydride is selected from any one of succinic anhydride, maleic anhydride, phthalic anhydride and glutaric anhydride.

[0010] The mass proportions of TiO2 aerogel, triethylamine, dibasic acid anhydride, N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and PEI are 5-10 parts, 0.01-1 parts, 0.5-5 parts, 0.1-5 parts, 0.1-5 parts and 1-50 parts.

[0011] The mass ratio of polyoxymethylene to PEI-TiO2 aerogel is 100:0.5-10.

[0012] The preparation of weather-resistant polyoxymethylene also includes light stabilizers and ultraviolet absorbers; The light stabilizer is any one of bis-2,2,6,6-tetramethylpiperidinol sebacate (Tinuvin770), poly[1-(2'-hydroxyethyl)-2.2.6.6-tetramethyl-4-hydroxypiperidinyl succinate] (Tinuvin622), and light stabilizer 783; the ultraviolet absorber is any one of 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole (UV-234), 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-327), 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole (UV-328), and 2-(2-hydroxy-5-methylphenyl)benzotriazole (UV-P).

[0013] The melt mixing temperature is 150-210°C, and the stirring speed is 50-200 rpm.

[0014] In some embodiments, the PEI-TiO2 aerogel preparation method is as follows: 10 parts of butyl titanate and 100-300 parts of anhydrous ethanol are uniformly mixed in a certain proportion, and 100-300 parts of anhydrous ethanol and 20-60 parts of deionized water are uniformly mixed, the pH of the solution is adjusted to 2 with acid, and it is slowly added dropwise to the prepared ethanol solution of butyl titanate at room temperature, followed by adding dropwise 3-10 parts of formamide and stirring evenly to obtain colorless and transparent TiO2 alcohol gel, which is aged for 6-48 h, then soaked in anhydrous ethanol for 12-48 h, dried at room temperature for 24-72 h, vacuum dried at 60°C for 12-72 h, and vacuum dried at 120°C for 6-24 h to obtain TiO2 aerogel.

[0015] Further, 10 parts of TiO2 aerogel are added to 100-1000 parts of dimethyl sulfoxide, the temperature is raised to 50-80°C, 0.01-1 parts of triethylamine and 0.5-5 parts of dibasic acid anhydride are added, and the reaction is carried out for 0.5-10 hours to obtain carboxylated TiO2 aerogel; the solution is cooled to room temperature, 0.1-5 parts of N-hydroxysuccinimide (NHS) and 0.1-5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) are added, and the mixture is stirred evenly, and then 1-50 parts of PEI are added, and the reaction is carried out for 0.5-5 hours to obtain PEI-grafted TiO2 aerogel, i.e. PEI-TiO2 aerogel, which is crushed for standby use; the dibasic acid anhydride is any one of succinic anhydride, maleic anhydride, phthalic anhydride, and glutaric anhydride.

[0016] In some embodiments, the method for preparing the weather-resistant polyoxymethylene is as follows: Add 100 parts of polyoxymethylene, 0.05-5 parts of light stabilizer, 0.05-5 parts of ultraviolet absorber and 0.5-10 parts of PEI-TiO2 aerogel particles into a high-speed mixer and mix them evenly. Then use a twin-screw extruder to melt-mix and extrude into granules. The screw speed is 50-200 rpm and the barrel temperature is 150-210°C to obtain weather-resistant polyoxymethylene.

[0017] The present invention has the following advantages: In view of the urgent need for practical application of weather-resistant polyoxymethylene, the present invention provides a weather-resistant polyoxymethylene and a preparation method thereof, which have the following characteristics: Aerogel material has a porous structure, extremely high porosity and specific surface area. The ultraviolet shielding agent TiO2 is made into an aerogel with a porous structure, and polyethyleneimine (PEI) is grafted onto the aerogel. It can not only form enhanced multiple absorption, reflection and shielding effects on ultraviolet rays, but also the porous structure and ultra-large specific surface area of ​​the aerogel are conducive to the strong adsorption of formaldehyde. At the same time, the large number of amino groups introduced have a reactive absorption and scavenging effect on the formaldehyde produced by the photodegradation of polyformaldehyde, thereby inhibiting the further degradation of polyformaldehyde. By compounding it with polyformaldehyde, light stabilizers, ultraviolet absorbers, etc., a polyformaldehyde composite material with excellent anti-ultraviolet and weathering properties can be obtained. DETAILED DESCRIPTION

[0018] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the contents of the present invention.

[0019] Example 1 10 parts of butyl titanate and 200 parts of anhydrous ethanol were uniformly mixed in a certain proportion, and 150 parts of anhydrous ethanol and 30 parts of deionized water were uniformly mixed, and the pH of the solution was adjusted to 2 with acid, and then it was slowly added to the prepared butyl titanate ethanol solution at room temperature, and then 5 parts of formamide were added, and stirred evenly to obtain colorless and transparent TiO2 alcohol gel, which was aged for 10 hours, and then soaked in anhydrous ethanol for 20 hours, dried at room temperature for 48 hours, vacuum dried at 60°C for 24 hours, and vacuum dried at 120°C for 12 hours to obtain TiO2 aerogel; Further, 10 parts of TiO2 aerogel were added to 300 parts of dimethyl sulfoxide, the temperature was raised to 60°C, 0.1 parts of triethylamine and 2 parts of succinic anhydride were added, and the reaction was carried out for 2 hours to obtain carboxylated TiO2 aerogel; the solution was cooled to room temperature, 0.5 parts of N-hydroxysuccinimide (NHS) and 0.7 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) were added, and the mixture was stirred evenly, and then 20 parts of PEI were added and the reaction was carried out for 1 hour to obtain PEI-grafted TiO2 aerogel, i.e. PEI-TiO2 aerogel, which was crushed for standby use; 100 parts of polyoxymethylene, 0.5 parts of Tinuvin770, 0.3 parts of 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-327), and 3 parts of PEI-TiO2 aerogel particles are added into a high-speed mixer and mixed evenly, then melt-kneaded and extruded into granules using a twin-screw extruder, with a screw speed of 150 rpm and a barrel temperature of 160-200°C to obtain weather-resistant polyoxymethylene. After 1000 hours of xenon lamp aging, the retention rates of tensile strength, flexural strength and modulus reach 100-110%, the retention rate of elongation at break reaches 65-70%, and the retention rate of notched impact strength reaches more than 90%.

[0020] Example 2 10 parts of butyl titanate and 180 parts of anhydrous ethanol were uniformly mixed in a certain proportion, and 200 parts of anhydrous ethanol and 40 parts of deionized water were uniformly mixed, and the pH of the solution was adjusted to 2 with acid, and then it was slowly added dropwise to the prepared butyl titanate ethanol solution at room temperature, and then 7 parts of formamide were added dropwise and stirred evenly to obtain colorless and transparent TiO2 alcohol gel, which was aged for 20 h, then soaked in anhydrous ethanol for 40 h, dried at room temperature for 30 h, vacuum dried at 60°C for 20 h, and vacuum dried at 120°C for 16 h to obtain TiO2 aerogel; Further, 10 parts of TiO2 aerogel were added to 500 parts of dimethyl sulfoxide, the temperature was raised to 70°C, 0.5 parts of triethylamine and 4 parts of glutaric anhydride were added, and the reaction was carried out for 5 hours to obtain carboxylated TiO2 aerogel; the solution was cooled to room temperature, 0.8 parts of N-hydroxysuccinimide (NHS) and 1 part of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) were added, and the mixture was stirred evenly, and then 30 parts of PEI were added and the reaction was carried out for 2 hours to obtain PEI-grafted TiO2 aerogel, i.e. PEI-TiO2 aerogel, which was crushed for standby use; 100 parts of polyoxymethylene, 0.3 parts of light stabilizer 783, 0.3 parts of 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole (UV-234), and 5 parts of PEI-TiO2 aerogel particles are added into a high-speed mixer and mixed evenly, then melt-kneaded and extruded into granules using a twin-screw extruder, with a screw speed of 200 rpm and a barrel temperature of 170-210°C to obtain weather-resistant polyoxymethylene. After 1000h of xenon lamp aging, the retention rates of tensile strength, flexural strength and modulus reach 115-120%, the retention rate of elongation at break reaches 65-70%, and the retention rate of notched impact strength reaches more than 92%.

[0021] Example 3 10 parts of butyl titanate and 150 parts of anhydrous ethanol were uniformly mixed in a certain proportion, and 250 parts of anhydrous ethanol and 50 parts of deionized water were uniformly mixed, and the pH of the solution was adjusted to 2 with acid, and then it was slowly added to the prepared butyl titanate ethanol solution at room temperature, and then 4 parts of formamide were added and stirred evenly to obtain colorless and transparent TiO2 alcohol gel, which was aged for 40 hours, and then soaked in anhydrous ethanol for 30 hours, dried at room temperature for 24 hours, vacuum dried at 60℃ for 20 hours, and vacuum dried at 120℃ for 30 hours to obtain TiO2 aerogel; Further, 10 parts of TiO2 aerogel were added to 700 parts of dimethyl sulfoxide, the temperature was raised to 60°C, 0.3 parts of triethylamine and 3 parts of phthalic anhydride were added, and the reaction was carried out for 7 hours to obtain carboxylated TiO2 aerogel; the solution was cooled to room temperature, 0.3 parts of N-hydroxysuccinimide (NHS) and 0.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) were added, and the mixture was stirred evenly, and then 35 parts of PEI were added and the reaction was carried out for 4 hours to obtain PEI-grafted TiO2 aerogel, i.e. PEI-TiO2 aerogel, which was crushed for standby use; 100 parts of polyoxymethylene, 0.4 parts of poly[1-(2'-hydroxyethyl)-2.2.6.6-tetramethyl-4-hydroxypiperidinyl succinate] (Tinuvin622), 0.5 parts of 2-(2-hydroxy-5-methylphenyl)benzotriazole (UV-P), and 2 parts of PEI-TiO2 aerogel particles are added into a high-speed mixer and mixed evenly, then melt-kneaded and extruded into granules using a twin-screw extruder, with a screw speed of 180 rpm and a barrel temperature of 160-190°C to obtain weather-resistant polyoxymethylene. After 1000h of xenon lamp aging, the retention rates of tensile strength, flexural strength and modulus reach 100-110%, the retention rate of elongation at break reaches 65-70%, and the retention rate of notched impact strength reaches more than 90%.

[0022] Comparative Example 100 parts of polyoxymethylene, 0.5 parts of Tinuvin770, 0.3 parts of 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-327), and 3 parts of TiO2 particles are added into a high-speed mixer and mixed evenly, then melt-kneaded and extruded into granules using a twin-screw extruder, with a screw speed of 150 rpm and a barrel temperature of 160-200°C. The obtained weather-resistant polyoxymethylene is subjected to 1000h of xenon lamp aging, and its tensile strength, flexural strength and modulus retention rates reach 100-105%, while the elongation at break retention rate is only 45%, and the notched impact strength retention rate is 75%.

Claims

1. A method for preparing weather-resistant polyoxymethylene, characterized in that: The polyoxymethylene preparation method comprises the following steps: PEI-TiO2 aerogel preparation: The TiO2 aerogel is added to a solvent, the temperature is raised to 50-80°C, triethylamine and dibasic acid anhydride are added, and a reaction is performed to obtain a carboxylated TiO2 aerogel; N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added to the carboxylated TiO2 aerogel, the mixture is stirred evenly, and then polyetherimide PEI is added to react to obtain a PEI-grafted TiO2 aerogel, i.e., PEI-TiO2 aerogel; Preparation of weather-resistant polyoxymethylene: The polyoxymethylene and PEI-TiO2 aerogel particles are uniformly mixed at high speed, melt-kneaded, extruded and granulated to obtain weather-resistant polyoxymethylene.

2. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The TiO2 aerogel is prepared by hydrolyzing a titanate alcohol solution under acidic conditions, adding formamide, and stirring to obtain a TiO2 alcohol gel. The obtained TiO2 alcohol gel is aged, soaked in an alcohol solution, and vacuum dried to obtain a TiO2 aerogel.

3. The method for preparing weather-resistant polyoxymethylene according to claim 2, characterized in that: The alcohol solution is selected from C1-C4 alcohol solutions.

4. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The dibasic acid anhydride is selected from any one of succinic anhydride, maleic anhydride, phthalic anhydride and glutaric anhydride.

5. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The mass proportions of TiO2 aerogel, triethylamine, dibasic acid anhydride, N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and PEI are 5-10 parts, 0.01-1 parts, 0.5-5 parts, 0.1-5 parts, 0.1-5 parts and 1-50 parts.

6. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The mass ratio of polyoxymethylene to PEI-TiO2 aerogel is 100:0.5-10.

7. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The preparation of weather-resistant polyoxymethylene also includes light stabilizers and ultraviolet absorbers; The light stabilizer is any one of bis-2,2,6,6-tetramethylpiperidinol sebacate (Tinuvin770), poly[1-(2'-hydroxyethyl)-2.2.6.6-tetramethyl-4-hydroxypiperidinyl succinate] (Tinuvin622), and light stabilizer 783; The ultraviolet absorber is any one of 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole (UV-234), 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-327), 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole (UV-328), and 2-(2-hydroxy-5-methylphenyl)benzotriazole (UV-P).

8. The method for preparing weather-resistant polyoxymethylene according to claim 1, characterized in that: The melt mixing temperature is 150-210°C, and the stirring speed is 50-200 rpm.